1996
DOI: 10.1007/bf00262805
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cyclo-oxygenase inhibition on ozone-induced respiratory inflammation and lung function changes

Abstract: Inhalation of O3 causes airways neutrophilic inflammation accompanied by other changes including increased levels of cyclo-oxygenase products of arachidonic acid in bronchoalveolar lavage fluid (BALF). Ozone O3 exposure also causes decreased forced vital capacity (FVC) and forced expiratory volume after 1 s (FEV(1)), associated with cough and substernal pain on inspiration, and small increases in specific airway resistance (SRAW). The spirometric decrements are substantially blunted by pretreatment with indome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 30 publications
4
36
1
Order By: Relevance
“…TNFα receptor binding activates several downstream signaling molecules including the transcription factor NF-κB, which regulates the activity of inflammatory genes implicated in ozone toxicity including nitric oxide synthase-2 and cyclooxygenase-2 (Hazucha et al, 1996;Fakhrzadeh et al, 2002). We have previously shown that alveolar macrophages from mice with a targeted disruption of NF-κB p50 do not generate reactive nitrogen intermediates and that these mice are protected from ozone toxicity (Fakhrzadeh et al, 2004b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TNFα receptor binding activates several downstream signaling molecules including the transcription factor NF-κB, which regulates the activity of inflammatory genes implicated in ozone toxicity including nitric oxide synthase-2 and cyclooxygenase-2 (Hazucha et al, 1996;Fakhrzadeh et al, 2002). We have previously shown that alveolar macrophages from mice with a targeted disruption of NF-κB p50 do not generate reactive nitrogen intermediates and that these mice are protected from ozone toxicity (Fakhrzadeh et al, 2004b).…”
Section: Resultsmentioning
confidence: 99%
“…A number of biochemical signaling molecules have been implicated in TNFα-induced activation of NF-κB including PI3K and its downstream target, PKB (Hazucha et al, 1996;Wallach et al, 1999;Grivennikov et al, 2006), and expression of these proteins was analyzed next. Alveolar macrophages from air-exposed wild type mice were found to express low levels of PI3K and PKB as determined by western blotting and immunocytochemistry (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cyclo-oxygenase products of arachidonic acid stimulate these receptors which are released on exposure to ozone [30,31]. Vitamins C and E have been shown to affect this arachidonic acid metabolism, but the role of antioxidants in this mechanism is not fully understood [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…IN HUMANS, EXPOSURE TO OZONE (O 3 ), a common air pollutant and powerful oxidant, causes substernal irritation, cough, decrements in pulmonary function, and airway hyperresponsiveness (AHR) to nonspecific bronchoconstricting agonists such as methacholine (MCh) (6,10,25,33). Even O 3 concentrations below the current U.S. Environmental Protection Agency standard are sufficient to initiate symptoms in children with asthma (30).…”
mentioning
confidence: 99%
“…Molecular changes include an increase in the production and/or expression of prostaglandins (PGE 2 , PGF 2␣ , 6-keto-PGF 1␣ , and 8-epi-PGF 2␣ ) (3,32,33,36), cytokines (IL-1␤, IL-6, and TNF-␣) (4,39,54,55,59,60), and chemokines [eotaxin, interferon-␥-inducible protein (IP-10), monocyte chemoattractant protein (MCP)-1, MCP-3, macrophage inflammatory protein (MIP)-1␣, KC, and MIP-2] (20,38,39,49,59,60,69). Cellular changes include sloughing of epithelial cells and neutrophil emigration into the air spaces (5, 12, 16, 20, 22, 49, 59 -61, 69).…”
mentioning
confidence: 99%